The Influence of Menu Variations, Location, and Service Quality on Consumer Purchasing Decisions at Terrace Brasserie in Canggu, Badung Regency - Ni Luh Putu Mutiara Utami SANJAYA; Ida Bagus Agung DHARMANEGARA; Ni Ketut SARIANI (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:This research aims to test and analyze the influence of menu variations, location and service quality on purchasing decisions.Methodology:This research was conducted at Terrace Brasserie Canggu with a significant research sample 100 respondents were taken using the Slovin formula. All data obtained from the distribution of the questionnaires are suitable for use. The data were then analyzed using multiple linear regression and hypothesis testing (t-test and f-test).Findings:The results of this research show that (1) Menu variations, location and service quality have a positive and significant effect on purchasing decisions at Terrace Brasserie Canggu, (2) Menu variations have a positive and significant effect on purchasing decisions at Terrace Brasserie Canggu. It means that the more menu variations there are, the more purchasing decisions at Terrace Brasserie Canggu will increase. (3) Location positively and significantly affects purchasing decisions at Terrace Brasserie Canggu. It means that the more strategically the location is, the more purchasing decisions at Terrace Brasserie Canggu will increase. (4) Service quality positively and significantly affects purchasing decisions at Terrace Brasserie Canggu.Implication:This means that the more service quality increases, the more purchasing decisions at Terrace Brasserie Canggu will increase.